Emergency surgery: the big three – abdominal aortic aneurysm, laparotomy and hip fracture. (January 2014) - Stoneham, M.; Murray, D.; Foss, N.
Summary: National reports recommended that peri‐operative care should be improved for elderly patients undergoing emergency surgery. Postoperative mortality and morbidity rates remain high, and indicate that emergency ruptured aneurysm repair, laparotomy and hip fracture fixation are high‐risk procedures undertaken on elderly patients with limited physiological reserve. National audits have reported variations in care quality, data that are increasingly being used to drive quality improvement through professional guidance. Given that the number of elderly patients presenting for emergency surgery is likely to rise as the population ages, this review summarises the evidence on which such guidance is based, and provides information about how anaesthetists might participate in audit and research aimed at improving local and national outcomes for these most vulnerable of patients.